2020
DOI: 10.1021/acs.jnatprod.0c00443
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Lignans from Hypoestes aristata

Abstract: Phytochemical investigation of extracts of the stems of Hypoestes aristata led to the isolation of nine lignans that included four known compounds, namely, hinokinin (1), savinin (2), medioresinol (3), and two cubebins (8a,b), three new butyrolactone lignans (4−6), and butyrolactol lignans 7a−c. The structures of the new compounds were established using 1D and 2D NMR and HRESIMS data. The absolute configurations of the new lignans were determined from their ECD data and the Mosher's ester method. This is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…H-8 and H-8' was assumed to be trans based on 3 J 8,8' = 5.4. [10] The configuration of H-7 and H-8, H-7' and 8' were determined to be cis according to HÀ H coupling constants (J 7,8 = 4.5, J 7',8' = 3.5). The experimental ECD spectrum of compound 1 agreed with its calculated data of (7S,8R,7'S,8'S) configuration (Figure 3), thus the absolute configuration of compound 1 (structure shown in Figure 1) was elucidated as (7S,8R,7'S,8'S) and given the name canjanolignan A. which suggested that compound 2 was also a dibenzylbutyrolactone lignan but with a different configuration or conformer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H-8 and H-8' was assumed to be trans based on 3 J 8,8' = 5.4. [10] The configuration of H-7 and H-8, H-7' and 8' were determined to be cis according to HÀ H coupling constants (J 7,8 = 4.5, J 7',8' = 3.5). The experimental ECD spectrum of compound 1 agreed with its calculated data of (7S,8R,7'S,8'S) configuration (Figure 3), thus the absolute configuration of compound 1 (structure shown in Figure 1) was elucidated as (7S,8R,7'S,8'S) and given the name canjanolignan A. which suggested that compound 2 was also a dibenzylbutyrolactone lignan but with a different configuration or conformer.…”
Section: Resultsmentioning
confidence: 99%
“…Its relative configuration was solved by H−H coupling constants. H‐8 and H‐8′ was assumed to be trans based on 3 J 8,8′ =5.4 [10] . The configuration of H‐7 and H‐8, H‐7′ and 8′ were determined to be cis according to H−H coupling constants ( J 7,8 =4.5, J 7′,8′ =3.5).…”
Section: Resultsmentioning
confidence: 99%
“…4 (20 mg) was also subjected to LC-SPE to afford compounds 2 (0.5 mg), 3 (0.6 mg), and 4 (0.6 mg). To accumulate more 50 with modifications of the HPLC method to facilitate the separation of the current fractions. To accumulate more material, some of the fractions were re-purified using prep-HPLC coupled to a PDA detector and a fraction collector (Waters, Milford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Incidentally, Melnikov and coworkers have observed this kind of rearrangement in a D–A cyclopropane containing an aryl donor and a diester acceptor. 8 It should be noted that γ-butyrolactones are structural subunits in a large number of natural products 9 and medicinally important compounds 10 and hence several methods have been reported for their synthesis. 11…”
Section: Introductionmentioning
confidence: 99%